New species and new records of freshwater Heterolepidoderma (Gastrotricha: Chaetonotidae) from Brazil with an identification key to the genus - Garraffoni, André R. S.; Melchior, Marina P. (Zootaxa, 2015)
A new species of freshwater Heterolepidoderma (Gastrotricha) was found in Brazil. Heterolepidoderma mariae sp. nov. is unique in possessing a three-lobed head, three types of dorsal keeled scales, a thin band of cilia on the head, connecting the two bands of ventral cilia, and an interciliary area with elliptical keeled scales with short spines. Heterolepidoderma famaillense Grosso & Drahg, 1991 is reported for the first time outside the type locality in Argentina, and we make some initial remarks on H. aff. majus Remane, 1927, a possible undescribed species. A dichotomous key for all freshwater species of Heterolepidoderma , with distributional data, is also provided.